PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY (TS-TS) TERHADAP KEMAMPUAN MENGANALISIS PUISI “KARANGAN BUNGA” KARYA TAUFIQ ISMAIL SISWA KELAS X SMA IT INDAH MEDAN - Rika Kartika (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2019)
Abstract. The purpose of this study is to describe the two say two stray learning model towards analyzing the poem "Karangan Bunga" by Taufiq Ismail class x SMA Indah Medan. The method used in this study is an experimental method that is the two group design post-test method. The instrument used was an essay test or written test that analyzed the poem "Karangan bunga" by Taufiq Ismail. From the results of data processing the average experimental class was 76.87 with a standard deviation of 9.90, while the control class 56 with a standard deviation of 8.15. Thus it can be said that the value of the experimental class is higher than the control class. After testing the hypothesis obtained tcount = 10.33 then consulted with a table at a significant level of 5% with dk = (n1 + n2) - 2 = (40 + 40-2) = 78, then obtained a significant level of 5% = 1.982 (with interpolation). Then compared between tcount with ttable obtained tcount> ttable 10.33> 1.982 so it can be concluded that Ha is accepted namely stating that the two say two stray model can be applied to improve students' abilities in analyzing the poem "Karangan bunga" by Taufiq Ismail to class X SMA IT Indah Medan. Keywords:  Two Say Two Stray Learning Model (TS-TS), Analyzing Poetry, Karangan bunga